Metodologias para avaliação da distribuição espacial da fusariose em pimenta-do-reino - Brumat, Ana Carolina Lyra (2018)
The spatiotemporal study of plant disease analyzes the interaction between of the pathogen, environment and the host, in which there are several methodologies that can be used for this purpose. However, fusariosis is considered the main fungal disease in bllack pepper crop, however there are still few epidemiological studies of this disease. The objective of this study was to study the spatial distribution of fusariosis in black pepper using different methodologies. Four homogeneous areas of black pepper were monitored in the municipality of São Mateus-ES, from December 2015 to December 2016. The presence or absence of symptoms, as well as the position of each plant, were recorded in spreadsheets and mapping the evolution of the disease in each area. For the spatial study the data were analyzed by different methodologies: Dispersion Index (ID), modified Taylor's Law, dynamics analysis and focus structure (ADEF), and kriging. Data analysis by means of modified Taylor's law indicated aggregate distribution only for area four. The ADEF showed that, with the evolution of the ix disease in the field, the outbreaks became larger and in smaller numbers. With the use of geostatistics, it was possible to observe that the fusariosis is disseminated at short distance, and that the foci obey a pattern of stretching. Comparing the results obtained by the different methods, it is possible to observe that the geostatistics has confirmed the results presented by the conventional methodologies (modified Taylor law and ADEF), and that it has potential to be used in the spatial study of plant diseases.